PENGEMBANGAN SISTEM INFORMASI KLINIK BERBASIS WEB - Wahyudi, Sri (Riau Journal Of Computer Science, 2020)
The process of inputting and storing patient data carried out for registration at the Surya Medika Pasir Pengaraian clinic is still done securely, as well as making reports for the leadership is still done manually which is handwritten notes. This is less helpful in the service process for customers to be ineffective because it is done manually. Seeing the activities of Surya Medika Pasir Pengaraian such as this, it is necessary to pay attention to the work system that is done manually so that it is converted into a computerized work system and uses Client Server technology. This research was conducted using the System Life Cycle Development (SDLC) method, namely using interviews and literature studies to find out the components involved in it